Biophysical and human factors determine the distribution of poached elephants in Tsavo East National Park, Kenya - Kyale, Daniel; Ngene, Shadrack; Maingi, John (Pachyderm, 2011)
This study investigates the distribution of poached elephants as well as the biophysical and anthropogenic factors that determine the distribution of the poached elephants in Tsavo East National Park (TENP), Kenya. Data on the distribution of poached elephants, from 1990 to 2005, were acquired from elephant mortality database of the Kenya Wildlife Service (KWS). The distribution of poached elephants was not random but exhibited a clustered pattern. Poaching of elephants was higher in the central and northern areas of TENP. Poaching hotspots occurred along the main rivers (i.e. Tiva, Galana and Voi Rivers). During the wet season, a high density of poached elephants was recorded within the grassland, bushland and open bushland. In the dry season, the density of poached elephants was highest in the woodland, bushland, open bushland and grassland environments. The distribution of poached elephants was significantly correlated with land cover, proximity to main rivers, surface water, ranger patrol bases, park gates, roads and park boundaries. Priority security patrols should be performed along the Galana, Tiva and Voi Rivers. Key words: Elephant distribution, physical and human factors, mortality, poaching Cette étude examine la répartition des éléphants braconnés, ainsi que les facteurs biophysiques et anthropiques qui déterminent la répartition des éléphants braconnés dans le Parc National de Tsavo Est, au Kenya. Les données sur la répartition des éléphants braconnés, de 1990 à 2005, ont été acquises à partir de la base de données du Service Kenyan de la Faune (KWS) sur la mortalité des éléphants. La répartition des éléphants braconnés n’était pas aléatoire, mais présentait une configuration regroupée. Le braconnage des éléphants était plus élevé dans les zones centrales et septentrionales du parc. Les points névralgiques de braconnage se trouvaient le long des rivières principales (c.-à-d. Tiva, Galana, et Voi). Au cours de la saison pluvieuse, on a enregistré une forte densité d’éléphants braconnés dans les herbages, la brousse et la brousse ouverte. Pendant la saison sèche, la densité des éléphants braconnés était la plus élevée dans la forêt claire, la brousse, la brousse ouverte et les herbages. La répartition des éléphants braconnés avait une corrélation significative avec la couverture du sol, la proximité des principaux cours d’eau, les eaux de surface, les bases de patrouilles des écogardes, les entrées du parc, les routes et les limites du parc. Les patrouilles prioritaires de sécurité devraient s’effectuer le long des fleuves Galana, Tiva et Voi.